Effect of size on the electronic structure and optical properties of cubic CsPbBr₃ quantum dots - Chen, Qiran (2021)
The size effect on the electronic structure and optical properties of cubic CsPbBr3 perovskite quantum dots is investigated by using an 8-band k p model based on effective-mass envelope function theory with exciton binding energy consideration. Quantum dots with smaller size have larger bandgaps due to quantum confinement. The transition matrix element (TME) is also influenced by the size. The optical gain of such material is calculated by considering TME, Fermi factor, injected carrier density, quantum dot size, and dephasing rate. Higher density of injected carrier is needed for smaller quantum dot to get a positive optical gain. The peak of optical gain has a blue shift as the size of quantum dot decreases. When the carrier density increases for a quantum dot with certain size, a blue shift in emission peak position can be observed due to band filling effect. Smaller quantum dots have higher differential optical gain at carrier densities within certain range.